p21-ras effector domain mutants constructed by "cassette" mutagenesis. - Stone, J C (1988)
A series of mutations encoding single-amino-acid substitutions within the v-rasH effector domain were constructed, and the ability of the mutants to induce focal transformation of NIH 3T3 cells was studied. The mutations, which spanned codons 32 to 40, were made by a "cassette" mutagenesis technique that involved replacing this portion of the v-rasH effector domain with a linker carrying two BspMI sites in opposite orientations. Since BspMI cleaves outside its recognition sequence, BspMI digestion of the plasmid completely removed the linker, creating a double-stranded gap whose missing ras sequences were reconstructed as an oligonucleotide cassette. Based upon the ability of the mutants to induce focal transformation of NIH 3T3 cells, a range of phenotypes from virtually full activity to none (null mutants) was seen. Three classes of codons were present in this segment: one which could not be altered, even conservatively, without a loss of function (codons 32 and 35); one which retained detectable biologic activity with conservative changes but which lost function with more drastic substitutions (codons 36 and 40); and one which retained function even with a nonconservative substitution (codon 39).